Plus ça change, plus c'est la même chose - Flavio Bartmann (RAE: Revista de Administração de Empresas, 2019)
In 1572, a single data point, Tycho’s Supernova, showed that contrary to the accepted paradigm at the time, the heavens did indeed change (Wootton , 2015). Less than 40 years later, in 1610, Galileo Galilei published his sensational findings in Sidereus Nuncius, a short treatise that demonstrated the existence of stars not seen by the naked eye and revealed the nature of the Milky Way (Galilei,1610). Since then, data analysis has been central to scientific research and examples of its use in solving important and difficult problems have multiplied. At the age of 24, Carl Friedrich Gauss (1809) used least squares to correctly predict Ceres’ position in 1801 after it emerged from behind the Sun’s glare. A simple spatial analysis identified the source of the Broad Street cholera outbreak in London in 1854 (Snow, 1855). Between 1856 and 1863, careful estimation of frequencies allowed Gregor Mendel (1866) to determine the basic rules of heredity of physical traits in plants. In the late 1940’s, a large retrospective study led by Richard Doll and A. Bradford Hill (1950) demonstrated the strong link between smoking and lung cancer.